Evaluating the effectiveness of mobile-based defect management applications (DMAs) on homebuyer satisfaction in high-rise condominium projects - Kok Lim, Chong; Mustafa, Muhammad Hadi; Ahmad Salleh, Ahmad Fawwaz; Hanafi, Siti Nurul Izzati; Abdul-Samad, Zulkiflee (Planning Malaysia, 2025)
Malaysia’s high-rise condominium projects continue to grapple with construction defects, as many homebuyers report unresolved issues that adversely affect their satisfaction and trust. In response, Defect Management Apps (DMAs) have emerged as digital tools designed to streamline defect reporting and resolution processes. This study evaluates the effectiveness of DMAs in enhancing homebuyer satisfaction within Klang Valley’s high-rise housing market. A mixed-methods approach was employed, combining quantitative data from 191 survey respondents with qualitative insights from 20 semi-structured interviews. The results reveal several key patterns. First, the adoption of DMAs does not necessarily correlate with satisfaction; while users appreciate the convenience, they express frustration when underlying service delivery issues persist. Second, satisfaction decreases as defect counts rise, underscoring the number of defects increases, highlighting the critical role of effective back-end coordination in managing substantial volumes of complaints. Third, generational and experiential differences play a significant role. Additionally, DMA effectiveness is shaped by factors such as usability, responsiveness, communication transparency, and real-time tracking capabilities. This study concludes that technology alone cannot guarantee satisfaction; it hinges on how effectively digital platforms integrate with supportive service processes